Payment Schemes based on Seed Quality - Incentives for the Swedish farmer - Schroeder,Andreas (2019)
Payment and bonus schemes based on seed quality used by the Swedish agriculture cooperative Lantmännen is evaluated. Results from a farm and region/time fixed effect model show that the linear payment scheme for pulses (peas and beans) has approximately 15 percentage points lower quality compared to that used for grains when a common quality measure constructed for this research is used. Germination capacity is reduced by five percentage points and the probability of reaching the desired water content level is 20 percent lower for pulses compared to grains. The result for bonus schemes are inconclusive, but show signs of endogeneity from matching.
Keywords: incentives; seed quality; moral hazard; payment scheme